(untitled) (SADGAMAYA, 2026)
This project investigates industry-academia partnerships in Nepal to create competency-based curriculum that improve graduate employability. The study investigates the determinants propelling integrated curriculum design and evaluates the aspects affecting stakeholder engagement, considering the increasing disparity between academic outcomes and labor market requirements. Structured questionnaires employing a quantitative framework were administered to 65 educational and 162 corporate respondents from prominent Nepalese colleges and businesses. Logistic regression and factor analysis were employed to validate constructs and predict collaborative outcomes. The results show that there are big differences in how people see things: academic institutions have mixed attitudes on the importance of the curriculum and employability (α = .260–.407), whereas companies actively promote curriculum co-design and say there are critical skill gaps (α = .775). Two academic constructs displayed reliability: corporate contribution to learning (α = .661) and research collaboration (α = .603). Logistic regression shows that meaningful industry discussion is a strong predictor of collaborative curriculum practices. The study finds that institutional mechanisms, such as competency integration, curriculum advisory boards, and structured feedback loops, are essential to bridge the divide between academics and industry. Policy changes that institutionalize collaborative curriculum creation, incorporate industry-validated competencies, and encourage long-term research partnerships are some of the effects that will help generate graduates who are ready for the job market and meet market needs.